Legal Protection for Indonesia Ship Crew Working on Foreign Ship - Ayu Putri Rainah Petung Banjaransari (Fakultas Hukum, Universitas Internasional Batam, 2022)
There are many Indonesian workers who work in the marine and fisheries sector on foreign ships because their wages are four times the wages of working on Indonesian ships. By reason of high wages often the possible consequences that will occur are ignored. As a result, many undesirable things happened such as human trafficking, torture, ill-treatment, and even murder, as happened on the Chinese ship Fu Yuan Yu 1218 against the victims of Indonesian crew members. This research was conducted to determine the form of accountability from the Indonesian government in the case of the crew of the ship. This research method is a normative juridical method with a qualitative approach and indirect observation and documentation. The findings of this research are in the form of an international legal basis regarding the rights of Indonesian crew members on foreign ships. In addition, this research also seeks legal protection from the Indonesian government based on national law for Indonesian crew members who work on foreign ships. This research is expected to contribute to providing new information regarding the implementation of Indonesian crew work on foreign ships.